2015
DOI: 10.1039/c4tx00135d
|View full text |Cite
|
Sign up to set email alerts
|

Impact of manganese on the hippocampus metabolism in the context of MEMRI: a proton HRMAS MRS study

Abstract: The HRMAS spectrum revealed an important impact of Mn 500 nmol on the hippocampal metabolism, not observed with Mn 8 nmol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(48 reference statements)
1
2
0
Order By: Relevance
“…This is consistent with our estimation that less than 0.01% of transcranially applied manganese reaches the brain, and that the average local concentrations of manganese in the ROIs in the brain rarely exceed 200 µM for the highest transcranially applied manganese concentration of 500 mM. Cellular studies indicate toxicity begins above the 200 µM manganese concentration in neural tissue (Daoust et al, 2015). …”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with our estimation that less than 0.01% of transcranially applied manganese reaches the brain, and that the average local concentrations of manganese in the ROIs in the brain rarely exceed 200 µM for the highest transcranially applied manganese concentration of 500 mM. Cellular studies indicate toxicity begins above the 200 µM manganese concentration in neural tissue (Daoust et al, 2015). …”
Section: Discussionsupporting
confidence: 90%
“…Next, 80 nL of Mn 2+ solution (or vehicle) were instilled at a rate of 8 nL • min −1 via a connected Hamilton syringe. It has been reported that Mn 2+ is not toxic at this concentration . Ten minutes after the end of the injection, the cannula was retracted stepwise to avoid leakage of the tracer along the injection track.…”
Section: Methodsmentioning
confidence: 99%
“…First, Mn 2+ dosing should be carefully optimized to minimize toxicity as well as ensure effective delivery to brain regions of interest. Several techniques for transporting Mn 2+ (typically in quantities of tens of nanomoles, corresponding to intracellular concentrations of 35–93 μM in the rodent brain) with minimum acute toxicity have already been established in the context of Mn 2+ enhanced MRI (MEMRI). These techniques include oral delivery, intraperitoneal administration, systemic injection, transcranial diffusion, and direct infusion in the cerebrospinal fluid. Although Mn 2+ can passively enter the brain parenchyma, transient and reversible opening of the blood brain barrier (e.g., using focused ultrasound) may be employed to augment the amount of Mn 2+ transported .…”
Section: Discussionmentioning
confidence: 99%